A three-dimensional / two-dimensional perovskite solar cell and its preparation method
By generating a <110> type two-dimensional perovskite layer on the three-dimensional perovskite surface, the problem of poor carrier transmission of two-dimensional perovskite is solved, and the efficiency and stability of perovskite solar cells are significantly improved, achieving more High photoelectric conversion efficiency and fill factor.
Patent Information
- Application Number
- CN202210438755.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-22
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-04-22
AI Technical Summary
The problem of poor carrier transport of two-dimensional perovskites in the three-dimensional/two-dimensional perovskite active layer limits the efficiency improvement of perovskite solar cells.
High-quality three-dimensional perovskite films are prepared by low-voltage auxiliary treatment, and a two-dimensional perovskite layer with <110> type is generated on the surface of the three-dimensional perovskite through a nonlinear long-chain organic amine salt solution to improve carrier transport performance .
The photoelectric conversion efficiency of perovskite solar cells has been significantly improved, the stability and open circuit voltage of the device have been improved, and the filling factor has also been improved.
Smart Images

Figure CN114883493B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor optoelectronic materials and devices, and specifically relates to a method based on three-dimensional / <110> Two-dimensional perovskite solar cell and its preparation method. Background Art
[0002] Organic-inorganic hybrid perovskite materials have attracted extensive research and developed rapidly due to their excellent photophysical properties. The photoelectric conversion efficiency of perovskite solar cells has increased from 3.8% in 2009 to 25.7% in 2022, which is close to the efficiency of single-crystal silicon cells, showing great application prospects. Currently, high-efficiency perovskite solar cells often use three-dimensional perovskites as active layers. However, the environmental stability of three-dimensional perovskites is poor, which seriously affects their commercialization. Compared with three-dimensional perovskites, two-dimensional perovskites have excellent humidity stability and thermal stability. Therefore, constructing a three-dimensional / two-dimensional perovskite active layer can effectively combine the excellent charge transport properties of three-dimensional perovskites and the advantages of high stability of two-dimensional perovskites, becoming an effective strategy for preparing high-performance perovskite photovoltaic devices.
[0003] In recent years, 3D / 2D perovskite active layers have made many encouraging progress in the field of optoelectronics. <100> This type of material has excellent humidity stability and thermal stability, which can significantly improve the long-term stability of the device. <100> The interlayer spacing of two-dimensional perovskites is large, and the carrier transport is poor, which limits the improvement of efficiency. The current methods to improve the carrier transport characteristics are to improve and develop from aspects such as interface modification and additives, thereby improving the efficiency of perovskite cells, but no research has been conducted from the perspective of the crystal structure of two-dimensional perovskites. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of poor carrier transport of two-dimensional perovskite in the current three-dimensional perovskite active layer, and propose a three-dimensional perovskite solar cell and its preparation method. The perovskite solar cell starts from the directionality of two-dimensional perovskite, selects <110> The two-dimensional perovskite is used as part of the active layer; the preparation method uses low-pressure auxiliary treatment to prepare high-quality three-dimensional perovskite film, and then treats it with a nonlinear long-chain organic amine salt solution to generate in situ on the surface of the three-dimensional perovskite. <110> The preparation method of the present invention is efficient and simple in preparation process. <110> The two-dimensional perovskite film has better film forming properties and fewer defects. The carrier transport performance of the perovskite solar cell prepared based on this is improved, and the photoelectric conversion efficiency is significantly improved, which has good application prospects in the future.
[0005] The technical solution of the present invention is:
[0006] A solar cell based on three-dimensional / two-dimensional perovskite, which comprises, from bottom to top, a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite active layer, a two-dimensional perovskite active layer, a hole transport layer and a counter electrode.
[0007] In the two-dimensional perovskite active layer, the structure of the two-dimensional perovskite is <110> The two-dimensional perovskite <110> The material of this type is BPbX4, where the B position is a nonlinear long-chain organic amine salt ion; the X position is F - , Cl - Br - ,I - At least one of .
[0008] The transparent conductive substrate is preferably one of fluorine tin oxide transparent conductive glass (FTO), indium tin oxide transparent conductive glass (ITO), PET / ITO (PET is polyethylene terephthalate), and PEN / ITO (PEN is polyethylene naphthalate).
[0009] The electron transport layer is tin dioxide (SnO2), titanium dioxide (TiO2), chlorine-doped titanium dioxide, carbon 60 (C 60 ), [6,6]-phenyl C61 butyric acid methyl ester (PCBM), zinc oxide (ZnO), TiO2-SnO2, ZnO-TiO2, ZnO-SnO2, with a thickness of 5 to 180 nm.
[0010] The hole transport layer is at least one of 2,2',7,7'-tetrakis(diphenylamino)-9,9'-spirobifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), gallium acetylacetonate, molybdenum trioxide (MoO3), and copper phthalocyanine (CuPc), and has a thickness of 0 or 5 to 200 nm; when the thickness is 0, it means that there is no hole transport layer.
[0011] The counter electrode is one or more of carbon, gold, silver, chromium and copper; when it is metal, the thickness is 50-200nm, when it is carbon, the thickness is 5-200μm, and there may or may not be a hole transport layer.
[0012] The thickness of the three-dimensional perovskite is 200-1000 nm, and the thickness of the two-dimensional perovskite is 1-50 nm.
[0013] The method for preparing the three-dimensional / two-dimensional perovskite solar cell comprises the following steps:
[0014] 1) preparing an electron transport layer on a transparent conductive substrate; then using a spin coater to spin-coat a three-dimensional perovskite precursor solution, and then annealing after treatment with a low-voltage auxiliary device to obtain a three-dimensional perovskite layer; the concentration of the three-dimensional perovskite solution is 0.5 to 2 mol / L;
[0015] 2) Spin coating a nonlinear long-chain organic amine salt solution with a concentration of 0.1 to 5 mg / mL on the surface of the three-dimensional perovskite layer and annealing to form <110> Type 2D perovskite;
[0016] Among them, every 1 to 10 cm 2 10 to 500 μL of nonlinear long-chain organic amine salt solution is coated on the substrate; the solvent is one of isopropanol and ethanol.
[0017] The nonlinear long-chain organic amine salt is 2,2'-(ethylenedioxy)bisethylamine hydroiodide (EDBEI2), 2,2'-(ethylenedioxy)bisethylamine hydrochloride (EDBECl2), 2,2'-(ethylenedioxy)bisethylamine hydrobromide (EDBEBr2), N-methylethylenediamine dihydroiodide ((N-MEDA)I2), N-methylethylenediamine dihydrochloride ((N-MEDA)Cl2), N-methylethylenediamine dihydrobromide ((N-MEDA)Br2), N-(3-aminopropyl)imidazole hydroiodide (C6H 11 N3·2HI, API·2HI), N-(3-aminopropyl)imidazole hydrochloride (C6H 11 N3·2HCl, API·2HCl), N-(3-aminopropyl)imidazole hydrobromide (C6H 11 N3·2HBr, API·2HBr) or one or more thereof.
[0018] 3) A hole transport layer and a counter electrode are sequentially prepared on the two-dimensional perovskite; when the counter electrode is made of carbon, the counter electrode is directly prepared on the two-dimensional perovskite.
[0019] The three-dimensional perovskite material has a structural formula of APbX3, with a carboxamidinium cation (NH2CH=NH2 + , F.A. + ), methylamine cation (CH3NH3 + , M.A. + ) and cesium ions (Cs + ) one or more; X is F - , Cl - Br - ,I -At least one of; the solvent of the perovskite mixed solution includes one or more of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), acetonitrile (CAN), methylamine acetate, methylamine formate, methylamine butyrate, γ-butyrolactone, and methanol;
[0020] The three-dimensional perovskite in step 1) is treated with the low-pressure auxiliary equipment at a vacuum degree of 1 to 100 Pa for 1 to 60 seconds; the annealing is carried out at 50 to 300° C. for 1 to 60 minutes;
[0021] The spin coating speed of the nonlinear long-chain organic amine salt solution in step 2) is 2000-6000 rpm for 20-60 seconds; the annealing temperature for annealing to form two-dimensional perovskite is 25°C-300°C for 1-20 minutes.
[0022] The essential features of the present invention are:
[0023] After research, it was found that in the current technology, the 3D / 2D perovskite active layer does not take into account the directionality of the 2D perovskite. <100> Although the stability of the device can be improved, <100> The carrier transport properties of this type of perovskite are poor, which usually affects the device efficiency.
[0024] In the present invention, the two-dimensional perovskite in the three-dimensional / two-dimensional perovskite active layer is <110> type, <110> The type of two-dimensional perovskite not only has better stability, but also has better carrier transport properties. Therefore, based on three-dimensional / <110> Two-dimensional perovskite solar cells can significantly improve the stability of the device while increasing its photoelectric conversion efficiency.
[0025] Two-dimensional perovskites can be viewed as <100> , <110> as well as <111> Direction cutting (described <100> , <110> as well as <111> refers to the crystal face family), and inserting a large layer of organic diamine cations or two layers of staggered monoamine cations into each cut surface, so the two-dimensional perovskite formed is called <100> type, <110> Type and <111> Type two-dimensional perovskite. <100> The type of perovskite is relatively easy to prepare. Generally, large-sized organic cations can be generated by reacting with lead halides. <110> This type of perovskite can only be obtained by reacting a relatively special nonlinear long-chain organic amine salt with a lead halide. At present, there are literature reports that this type of material has good white light emission properties, but its application in solar cells has not been seen. Our research found that <110> Compared with the two-dimensional perovskite <100> The two-dimensional perovskite has better stability and carrier transport properties. <110> When the two-dimensional perovskite is used as the light-absorbing layer of a solar cell, firstly, the stability of the three-dimensional perovskite layer can be significantly improved. Secondly, the surface electronic structure of the three-dimensional perovskite can be changed, and its Fermi level can be increased, so that a larger built-in electric field is generated when it contacts the hole transport layer, thereby improving the carrier separation efficiency and reducing the open-circuit voltage loss caused by non-radiative recombination. In other words, it can ultimately not only improve the stability of the device, but also increase the open-circuit voltage of the device, thereby improving the photoelectric conversion efficiency of the device.
[0026] The beneficial effects of the present invention are:
[0027] 1. The three-dimensional / <110> The preparation method of the two-dimensional perovskite solar cell is simple, and the three-dimensional / two-dimensional perovskite film has good density and high quality, and is the preferred material for preparing perovskite solar cells;
[0028] 2. The present invention provides a three-dimensional / <110> Carbon electrode solar cells made of two-dimensional perovskite are better than those made of three-dimensional <100> The open circuit voltage of carbon electrode solar cells based on type two-dimensional perovskite is increased by 0.90%, the fill factor is increased by 28.38%, and the efficiency is increased by 30.56%. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the structure of the solar cell of the present invention; wherein 1 is a transparent conductive substrate, 2 is an electron transport layer, 3 is a three-dimensional perovskite active layer, 4 is a two-dimensional perovskite active layer, 5 is a hole transport layer, and 6 is a counter electrode;
[0030] Figure 2 is a scanning electron microscope image of the surface of the TiO2-SnO2 film prepared in Example 1;
[0031] Figure 3is a scanning electron microscope image of a cross section of the TiO2-SnO2 film prepared in Example 1;
[0032] Figure 4 is a scanning electron microscope image of the surface of the three-dimensional FAPbI3 perovskite film prepared in Example 1;
[0033] Figure 5 The three-dimensional FAPbI3 / prepared in Example 1 <110> Scanning electron microscopy image of the surface of the two-dimensional (EDBE) PbI4 perovskite film;
[0034] Figure 6 is a cross-sectional scanning electron microscope image of the carbon counter electrode in Example 1;
[0035] Figure 7 In Example 1, based on three-dimensional FAPbI3 / <110> JV curve of carbon electrode solar cell prepared by type two-dimensional (EDBE) PbI4 perovskite;
[0036] Figure 8 The three-dimensional MAPbI3 perovskite film in Example 2, <110> Type 2D (EDBE) PbI4 perovskite film and 3D MAPbI3 / <110> X-ray diffraction comparison of type two-dimensional (EDBE) PbI4 perovskite film;
[0037] Fig. 9 In Example 2, based on the three-dimensional MAPbI3 / <110> JV curve of carbon electrode solar cell prepared by type two-dimensional (EDBE) PbI4 perovskite;
[0038] Fig.10 It is based on the three-dimensional MAPbI3 / <110> JV curve of carbon electrode solar cell prepared by type two-dimensional (EDBE) PbBr4 perovskite;
[0039] Fig.11 In comparative example 1, the three-dimensional MAPbI3 / <100> JV curve of carbon electrode solar cells prepared with type two-dimensional (BDAD) PbI4 perovskite. DETAILED DESCRIPTION
[0040] The following embodiments can enable those skilled in the art to more fully understand the present invention, but the present invention is not limited to the scope of the embodiments.
[0041] Example 1.
[0042] Based on three-dimensional FAPbI3 / <110> The carbon electrode perovskite solar cell with two-dimensional (EDBE) PbI4 perovskite active layer is shown in the schematic diagram of its structure. Figure 1As shown, from bottom to top are a transparent conductive substrate 1, an electron transport layer 2, a three-dimensional perovskite active layer 3, a two-dimensional perovskite active layer 4, a hole transport layer 5 and a counter electrode 6. The specific preparation process is as follows:
[0043] Step 1: Clean the FTO substrate:
[0044] The FTO substrate was ultrasonically cleaned with glass cleaner, deionized water and alcohol for 10 minutes respectively, and then dried with a nitrogen gun.
[0045] Step 2: Preparation of electron transport layer TiO2-SnO2:
[0046] Prepare TiO2 growth solution: dissolve 0.5 mL of titanium tetrachloride (TiCl4) solution in a blue-mouth bottle containing 100 mL of condensed water, refrigerate and set aside.
[0047] Prepare SnO2 growth solution: Use a balance to weigh 625 mg urea and 137.5 mg SnCl2·2H2O and put them into a blue-mouth bottle. Then use a pipette to add 625 μL HCl, 12.5 μL TGA, and 50 mL deionized water, mix well, and set aside.
[0048] Immerse the FTO substrate in a dyeing dish filled with TiO2 growth solution, place it in a 70°C oven for 1.5 hours, take it out, and ultrasonically clean it with deionized water for 5 minutes; change to SnO2 growth solution, place it in a 90°C oven for 4 hours, take it out, and ultrasonically clean it with deionized water for 5 minutes; change to SnO2 growth solution again, place it in a 90°C oven for 3 hours, take it out, and ultrasonically clean it with deionized water for 5 minutes and blow it dry with an air gun; then anneal it (annealing temperature 170°C, annealing time 60 minutes) to obtain the electron transport layer TiO2-SnO2. The scanning electron microscope image of the surface of the prepared TiO2-SnO2 film is as follows Figure 2 The scanning electron microscope image of the cross section is shown in Figure 3 As shown in the figure, it can be seen that the surface of the TiO2-SnO2 film is dense and has no holes, and the thickness is 50nm.
[0049] Step 3: Preparation of three-dimensional FAPbI3 / <110> Type 2D (EDBE) PbI4 perovskite active layer:
[0050] A 1.25 mol / L FAPbI3 perovskite precursor solution was prepared. The concentration was based on the lead content and specifically included solute formamidine iodine, lead iodide, and methylamine chloride. The molar amounts were 1 mmol, 1 mmol, and 0.18 mmol, respectively. Solvents including 100 μL NMP and 700 μL DMF were added in sequence to obtain 800 μL of precursor solution.
[0051] Using a coating machine, a TiO2-SnO2 substrate (area 6.25cm 2 ) was spin-coated with the prepared perovskite precursor solution (spin-coating speed was 4000 rpm, and the spin-coating time was 8 seconds), and then immediately placed in a low-pressure auxiliary system (DL-10A quartz vacuum gauge and vacuum pump) for low-pressure (vacuum degree was 10Pa) treatment for 60 seconds to rapidly evaporate the solvent, thereby obtaining a well-crystallized intermediate phase film. After the low-pressure treatment, annealing was performed on a hot stage at 150°C for 20 minutes to obtain a well-crystallized three-dimensional FAPbI3 perovskite film. The volume of the spin-coated perovskite precursor was 60μL.
[0052] The EDBEI2 / isopropanol solution (volume 60 μL, concentration 0.66 mg / mL) was spin-coated on the three-dimensional perovskite layer FAPbI3 at a speed of 5000 rpm for 30 seconds, and then immediately placed on a hot plate at 100°C for annealing for 5 minutes. The upper layer of the FAPbI3 perovskite reacted in situ with EDBEI2 to form <110> Type 2D (EDBE) PbI4 perovskite layer, resulting in 3D FAPbI3 / <110> Type two-dimensional (EDBE) PbI4 perovskite active layer.
[0053] In this embodiment, the thickness of the three-dimensional FAPbI3 perovskite layer is 400nm. <110> The thickness of the two-dimensional (EDBE) PbI4 perovskite layer is 30nm.
[0054] Scanning electron microscope photos of the surface of the three-dimensional FAPbI3 perovskite film Figure 4 As shown in the figure, it can be seen that the prepared three-dimensional perovskite film is dense and has no holes, which is conducive to the preparation of high-performance optoelectronic devices. <110> Scanning electron microscope images of the surface of the two-dimensional (EDBE) PbI4 perovskite film Figure 5 As shown in the figure, it can be seen that the nonlinear long-chain organic amine salt solution reacts with the three-dimensional perovskite, changing the surface morphology of the three-dimensional perovskite film, indicating that the upper part of the three-dimensional perovskite reacts with the nonlinear long-chain organic amine salt solution in situ to form <110> Type two-dimensional perovskite layer.
[0055] Step 4: Preparation of hole transport layer P3HT:
[0056] The hole transport layer P3HT precursor solution was prepared, specifically including 20 mg P3HT as a solute, 1 mL dichlorobenzene as a solvent, 16 μL 4-tert-butylpyridine (tBP), and 30 μL Li-TFSI / CAN (170 mg / mL) as a solvent.
[0057] The hole transport layer P3HT precursor solution was spin-coated on the perovskite layer, with a spin-coating volume of 60 μL, a spin-coating speed of 4000 rpm, and a spin-coating time of 8 seconds. The thickness of the obtained hole transport layer was 50 nm.
[0058] Step 5: Preparation of carbon electrode:
[0059] Use a blade to scrape the low-temperature conductive carbon electrode slurry (square resistance <30 ohms, solid content 50%) on the hole transport layer and heat it on a hot plate at 120°C for 20 minutes to solidify it. The cross-sectional scanning electron microscopy image of the carbon counter electrode is shown in Figure 2. Figure 6 As shown in the figure, it can be seen that its thickness is 10μm.
[0060] The effective area of the perovskite solar cell in this embodiment is 0.09 cm 2 .
[0061] In this embodiment, a solar simulator is used to select a K-2400 light source to simulate AM 1.5G lighting based on a three-dimensional FAPbI3 / <110> The JV test of carbon electrode solar cells prepared by type two-dimensional (EDBE) PbI4 perovskite is carried out. Figure 7 As shown in the figure, the photoelectric conversion efficiency of the solar cell is 15.16%, and the open circuit voltage, short circuit current density and fill factor are 1.04V, 22.90mA / cm 2 and 63.59%.
[0062] Example 2.
[0063] Based on three-dimensional MAPbI3 / <110> Carbon-electrode perovskite solar cells with two-dimensional (EDBE) PbI4 perovskite active layer
[0064] The other steps are the same as those in Example 1, except that:
[0065] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.21 mol / L (based on the lead content), specifically including 1 mmol of solute methylamine iodine and 1 mmol of lead iodide, and the solvents DMF 750 μL and DMSO 72 μL are added in sequence to obtain 822 μL of precursor solution.
[0066] In this embodiment, based on the three-dimensional MAPbI3 / <110> Two-dimensional (EDBE) PbI4 perovskite film, three-dimensional MAPbI3 perovskite film and the same method prepared <110> X-ray diffraction comparison of type two-dimensional (EDBE) PbI4 perovskite film, such as Figure 8As shown in the figure, it can be seen that the three-dimensional MAPbI3 / <110> The peak of the (EDBE)PbI4 two-dimensional perovskite (020) surface at 6.14° proves that the upper part of the three-dimensional perovskite reacts with the nonlinear long-chain organic amine salt solution in situ to form <110> Type two-dimensional perovskite layer.
[0067] In this embodiment, based on the three-dimensional MAPbI3 / <110> The JV curve comparison of carbon electrode solar cells prepared by type two-dimensional (EDBE) PbI4 perovskite is shown in the figure Fig. 9 As shown, it can be seen that its photoelectric conversion efficiency is 16.45%, and the open circuit voltage, short circuit current density and fill factor are 1.12V, 22.57mA / cm 2 and 65.01%, which is significantly better than those reported previously.
[0068] Example 3.
[0069] Based on three-dimensional MAPbI3 / <110> The other steps of the carbon electrode perovskite solar cell with two-dimensional (EDBE) PbBr4 perovskite active layer are the same as those in Example 1, except that:
[0070] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.21 mol / L (based on the lead content), specifically including 1 mmol of solute methylamine iodine and 1 mmol of lead iodide, and the solvents DMF 750 μL and DMSO 72 μL are added in sequence to obtain 822 μL of precursor solution.
[0071] The nonlinear long-chain organic amine salt solution is an EDBEBr2 / isopropanol solution with a concentration of 0.66 mg / mL.
[0072] In this embodiment, based on the three-dimensional MAPbI3 / <110> The JV curve comparison of carbon electrode solar cells prepared by type two-dimensional (EDBE) PbBr4 perovskite is shown in the figure Fig.10 As shown, it can be seen that its photoelectric conversion efficiency is 16.13%, and the open circuit voltage, short circuit current density and fill factor are 1.14V, 22.63mA / cm 2 and 62.74%, which is also significantly better than those previously reported.
[0073] Example 4.
[0074] Based on three-dimensional FAPbI3 / <110> The other steps of the carbon electrode perovskite solar cell with two-dimensional (EDBE) PbCl4 perovskite active layer are the same as those in Example 1, except that:
[0075] The nonlinear long-chain organic amine salt solution is (EDBE)PbCl4 / isopropanol solution with a concentration of 0.30 mg / mL.
[0076] Example 5.
[0077] Based on three-dimensional FAPbI3 / <110> Hole-free carbon electrode perovskite solar cells with two-dimensional (EDBE) PbI4 perovskite active layer
[0078] The other steps are the same as those in Example 1, except that:
[0079] Perovskite solar cells have no hole transport layer. Their structure from bottom to top is FTO transparent conductive substrate, electron transport layer TiO2-SnO2, three-dimensional FAPbI3 / <110> Type two-dimensional (EDBE) PbI4 perovskite active layer and carbon electrode.
[0080] Example 6.
[0081] Based on three-dimensional FAPbI3 / <110> The other steps of the metal electrode perovskite solar cell with two-dimensional (EDBE) PbI4 perovskite active layer are the same as those in Example 1, except that:
[0082] The hole transport layer is Spiro-OMeTAD, which specifically includes 72.3 mg of solute Spiro-OMeTAD, 1 mL of solvent chlorobenzene, 12.5 μL of Li-TFSI / CAN (250 mg / mL), and 28 μL of tBP. The spin coating volume is 60 μL, the spin coating speed is 4000 rpm, and the spin coating time is 30 seconds.
[0083] The counter electrode was made of gold and was prepared by vacuum evaporation with a vacuum degree of 5×10 -4 Pa, evaporation rate is 0.01~0.08nm / s, and thickness is 80nm.
[0084] Perovskite solar cell has an active area of 0.1 cm 2 .
[0085] Example 7.
[0086] Based on three-dimensional MAPbI3 / <110> The other steps of the metal electrode perovskite solar cell with two-dimensional (EDBE) PbBr4 perovskite active layer are the same as those in Example 1, except that:
[0087] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.21 mol / L (based on the lead content), specifically including 1 mmol of solute methylamine iodine and 1 mmol of lead iodide, and the solvents DMF 750 μL and DMSO 72 μL are added in sequence to obtain 822 μL of precursor solution.
[0088] The nonlinear long-chain organic amine salt solution is an EDBEBr2 / isopropanol solution with a concentration of 0.66 mg / mL.
[0089] The hole transport layer is Spiro-OMeTAD, which specifically includes 72.3 mg of solute Spiro-OMeTAD, 1 mL of solvent chlorobenzene, 12.5 μL of Li-TFSI / CAN (250 mg / mL), and 28 μL of tBP. The spin coating volume is 60 μL, the spin coating speed is 4000 rpm, and the spin coating time is 30 seconds.
[0090] The counter electrode was made of gold, which was prepared by vacuum deposition with a vacuum degree of 5×10 -4 Pa, evaporation rate is 0.01-0.08nm / s, and thickness is 80nm.
[0091] Perovskite solar cell has an active area of 0.1 cm 2 .
[0092] Example 8.
[0093] Based on three-dimensional MAPbI3 / <110> Carbon-electrode perovskite solar cells with two-dimensional (N-MEDA) [PbBr4] perovskite active layer
[0094] The other steps are the same as those in Example 1, except that:
[0095] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.21 mol / L (based on the lead content), specifically including 1 mmol of solute methylamine iodine and 1 mmol of lead iodide, and the solvents DMF 750 μL and DMSO 72 μL are added in sequence to obtain 822 μL of precursor solution.
[0096] The nonlinear long-chain organic amine salt solution is a (N-MEDA)Br2 / isopropanol solution with a concentration of 0.5 mg / mL.
[0097] Example 9.
[0098] Based on three-dimensional MAPbI3 / <110> Carbon-electrode perovskite solar cells with two-dimensional (N-MEDA) [PbI4] perovskite active layer
[0099] The other steps are the same as those in Example 1, except that:
[0100] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.21 mol / L (based on the lead content), specifically including 1 mmol of solute methylamine iodine and 1 mmol of lead iodide, and the solvents DMF 750 μL and DMSO 72 μL are added in sequence to obtain 822 μL of precursor solution.
[0101] The nonlinear long-chain organic amine salt solution is a (N-MEDA)I2 / isopropanol solution with a concentration of 0.66 mg / mL.
[0102] Example 10.
[0103] Based on three-dimensional MAPbI3 / <110> Carbon-electrode perovskite solar cells with two-dimensional (N-MEDA) [PbCl4] perovskite active layer
[0104] The other steps are the same as those in Example 1, except that:
[0105] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.21 mol / L (based on the lead content), specifically including 1 mmol of solute methylamine iodine and 1 mmol of lead iodide, and the solvents DMF 750 μL and DMSO 72 μL are added in sequence to obtain 822 μL of precursor solution.
[0106] The nonlinear long-chain organic amine salt solution is a (N-MEDA)Cl2 / isopropanol solution with a concentration of 0.30 mg / mL.
[0107] Example 11.
[0108] Based on three-dimensional MAPbI3 / <110> Type 2D (C6H 13 N3) The other steps of the carbon electrode perovskite solar cell with PbBr4 perovskite active layer are the same as those in Example 1, except that:
[0109] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.21 mol / L (based on the lead content), specifically including 1 mmol of solute methylamine iodine and 1 mmol of lead iodide, and the solvents DMF 750 μL and DMSO 72 μL are added in sequence to obtain 822 μL of precursor solution.
[0110] The nonlinear long-chain organic amine salt solution is an API·2HBr / isopropanol solution with a concentration of 0.60 mg / mL.
[0111] Example 12.
[0112] Based on three-dimensional MAPbI3 / <110> Type 2D (C6H 13 N3) The other steps of the carbon electrode perovskite solar cell with PbI4 perovskite active layer are the same as those in Example 1, except that:
[0113] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.25 mol / L (based on the lead content), specifically including 1 mmol of solute methylamine iodine and 1 mmol of lead iodide, and the solvents DMF 750 μL and DMSO 72 μL are added in sequence to obtain 822 μL of precursor solution.
[0114] The nonlinear long-chain organic amine salt solution is an API·2HI / isopropanol solution with a concentration of 0.80 mg / mL.
[0115] Comparative Example 1.
[0116] Based on three-dimensional MAPbI3 / <100> The other steps of the carbon electrode perovskite solar cell with a two-dimensional (BDAD) PbI4 perovskite active layer are the same as those in Example 1, except that:
[0117] The three-dimensional perovskite layer is MAPbI3, and the concentration is 1.21 mol / L (based on the lead content), specifically including the solute methylamine iodine 1mM, lead iodide 1mM, and the solvents DMF 750μL and DMSO 72μL are added in sequence to obtain 822μL of precursor solution.
[0118] The long-chain organic amine salt used was a BDADI2 / isopropanol solution with a concentration of 0.66 mg / mL.
[0119] In this embodiment, based on the three-dimensional MAPbI3 / <100> The JV curve of the carbon electrode solar cell prepared by type two-dimensional (BDAD) PbI4 perovskite is shown in Fig.11 As shown in the figure, it can be seen that based on the three-dimensional MAPbI3 / <100> The photoelectric conversion efficiency of the solar cell with a two-dimensional (BDAD) PbI4 perovskite active layer is 12.60%, and the open circuit voltage, short circuit current density and fill factor are 1.11V, 22.41mA / cm 2 and 50.64%, which is significantly lower than that in Example 2 based on three-dimensional MAPbI3 / <110> Photovoltaic conversion efficiency of solar cells with type two-dimensional (EDBE) PbI4 perovskite active layer.
[0120] The above embodiments illustrate the three-dimensional <110> Solar cells made of two-dimensional perovskites can indeed significantly improve carrier transport performance and device efficiency, and have good application prospects in the field of photovoltaic devices.
[0121] The present invention is not limited to the above-mentioned embodiments, and may be varied within the scope of the claims. The above-mentioned embodiments and the description are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
[0122] Matters not covered by the present invention are known technologies.
Claims
1. A solar cell based on three-dimensional / two-dimensional perovskite, The solar cell is characterized in that from bottom to top, it comprises a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite active layer, a two-dimensional perovskite active layer, a hole transport layer and a counter electrode; In the two-dimensional perovskite active layer, the structure of the two-dimensional perovskite is <110> type; The two-dimensional perovskite <110> The material of this type is BPbX4, where the B position is a nonlinear long-chain organic amine salt ion; the X position is F - , Cl - Br - ,I - At least one of; The thickness of the hole transport layer of the solar cell is 0 or 5 to 200 nm; when the thickness is 0, it means there is no hole transport layer; The nonlinear long-chain organic amine salt is 2,2'-(ethylenedioxy)bisethylamine hydroiodide (EDBEI2), 2,2'-(ethylenedioxy)bisethylamine hydrochloride (EDBECl2), 2,2'-(ethylenedioxy)bisethylamine hydrobromide (EDBEBr2), N-methylethylenediamine dihydroiodide ((N-MEDA)I2), N-methylethylenediamine dihydrochloride ((N-MEDA)Cl2), N-methylethylenediamine dihydrobromide ((N-MEDA)Br2), N-(3-aminopropyl)imidazole hydroiodide (C6H 11 N3•2HI, API•2HI), N-(3-aminopropyl)imidazole hydrochloride (C6H 11 N3•2HCl, API•2HCl), N-(3-aminopropyl)imidazole hydrobromide (C6H 11 N3•2HBr) or more; The transparent conductive substrate is one of fluorine tin oxide transparent conductive glass (FTO), indium tin oxide transparent conductive glass (ITO), PET / ITO (PET is polyethylene terephthalate), and PEN / ITO (PEN is polyethylene naphthalate); The electron transport layer is tin dioxide (SnO2), titanium dioxide (TiO2), chlorine-doped titanium dioxide, carbon 60 (C 60 ), [6,6]-phenyl C61 butyric acid methyl ester (PCBM), zinc oxide (ZnO), TiO2-SnO2, ZnO-TiO2, ZnO- SnO2, with a thickness of 5-180 nm; The three-dimensional perovskite material has a structural formula of APbX3, and the A position is a carboxamidinium cation (NH2CH=NH2 + , F.A. + ), methylamine cation (CH3NH3 + , M.A. + ) and cesium ions (Cs + ) one or more; X is F - , Cl - Br - ,I - At least one of; The hole transport layer is at least one of 2,2',7,7'-tetrakis(diphenylamino)-9,9'-spirobifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), gallium acetylacetonate, molybdenum trioxide (MoO3), and copper phthalocyanine (CuPc); The counter electrode is one or more of carbon, gold, silver, chromium, and copper; when it is a metal, the thickness is 50-200 nm; when it is carbon, the thickness is 5-200 μm, with or without a hole transport layer.
2. The three-dimensional / two-dimensional perovskite-based solar cell according to claim 1, characterized in that The thickness of the three-dimensional perovskite is 200-1000 nm, and the thickness of the two-dimensional perovskite is 1-50 nm.
3. The method for preparing a three-dimensional / two-dimensional perovskite solar cell according to claim 1, characterized in that the method comprises the following steps: 1) preparing an electron transport layer on a transparent conductive substrate; then using a coating machine to spin-coat a three-dimensional perovskite solution, and then annealing after treatment with a low-voltage auxiliary device to obtain a three-dimensional perovskite layer; the concentration of the three-dimensional perovskite solution is 0.5-2 mol / L; The solvent of the perovskite mixed solution includes one or more of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), acetonitrile (CAN), methylamine acetate, methylamine formate, methylamine butyrate, γ-butyrolactone, and methanol; 2) Spin-coat a nonlinear long-chain organic amine salt solution with a concentration of 0.1-5 mg / mL on the surface of the three-dimensional perovskite layer and anneal to form <110> Type 2D perovskite; in, Every 1~10 cm 2 10-500 μL of nonlinear long-chain organic amine salt solution is coated on the substrate; the solvent is one of isopropanol and ethanol; 3) A hole transport layer and a counter electrode are sequentially prepared on the two-dimensional perovskite; when the counter electrode is made of carbon, a hole transport layer and a counter electrode are sequentially prepared on the two-dimensional perovskite, or the counter electrode is directly prepared on the two-dimensional perovskite.
4. The method for preparing a three-dimensional / two-dimensional perovskite solar cell according to claim 3, characterized in that the three-dimensional perovskite in step 1) is treated with the low-pressure auxiliary equipment at a vacuum degree of 1 to 100 Pa for 1 to 60 seconds; and the annealing is maintained at 50 to 300 °C for 1 to 60 minutes.
5. The method for preparing a three-dimensional / two-dimensional perovskite solar cell according to claim 3, characterized in that The spin coating speed of the nonlinear long-chain organic amine salt solution in step 2) is 2000-6000 rpm for 20-60 seconds; the annealing temperature for annealing to form a two-dimensional perovskite is 25°C-300°C for 1-20 minutes.